2020
DOI: 10.1093/arclin/acaa081
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Components of Metabolic Syndrome to Cognitive Performance in Middle-Aged Adults

Abstract: Introduction Metabolic syndrome (MetS) has been associated with impaired cognition in different cognitive domains. This study investigated the association between MetS and cognitive functioning in middle-aged Bulgarians across different definitions of MetS severity. Material and Methods Our cross-sectional sample included 112 participants (67 free of MetS and 45 with MetS) with a mean age of 50.04 ± 3.31 years. The following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…Although CERAD originally examined cognitive deficits commonly seen in Alzheimer's disease, such as memory impairment, disorientation, loss of expressive and receptive language, and dyspraxia ( 21 ), by adding the PLUS subtests the domains can be expanded so that the CERAD Plus batterie also appears suitable for assessing cognitive deficits of other causes. The CERAD Plus has been used for cognitive assessments in other degenerative diseases like Parkinson's disease ( 32 , 33 ), inflammatory diseases like Neuro-Sjögren's syndrome ( 34 ), in patients with microbleeds after stroke ( 35 ), or middle-aged adults with metabolic syndrome with total score ( 36 ) underlining its broad applicability.…”
Section: Discussionmentioning
confidence: 99%
“…Although CERAD originally examined cognitive deficits commonly seen in Alzheimer's disease, such as memory impairment, disorientation, loss of expressive and receptive language, and dyspraxia ( 21 ), by adding the PLUS subtests the domains can be expanded so that the CERAD Plus batterie also appears suitable for assessing cognitive deficits of other causes. The CERAD Plus has been used for cognitive assessments in other degenerative diseases like Parkinson's disease ( 32 , 33 ), inflammatory diseases like Neuro-Sjögren's syndrome ( 34 ), in patients with microbleeds after stroke ( 35 ), or middle-aged adults with metabolic syndrome with total score ( 36 ) underlining its broad applicability.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, metabolic syndrome is significantly associated with cognitive impairment in persons with schizophrenia [301]. Persons with metabolic syndrome perform considerably worse at cognitive performance tasks compared with those with no metabolic syndrome [302]. Metabolic syndrome was associated with a higher risk for cognitive impairment that was observed across several studies.…”
Section: Oxytocin Dysfunction As a Common Mechanism Underlying Schizo...mentioning
confidence: 96%
“…Alzheimer’s disease (AD) is the most common cause of senile dementia worldwide, characterized by both cognitive and behavioral deficit. Evidence has shown that metabolic syndrome drives blood-brain barrier impairment with neuroinflammation development paralleled by the accumulation of toxic amyloid, causing cognition impairment in different cognitive domains [ 65 , 66 ]. Aβ oligomers (AβO) are responsible for several pathological mechanisms during the development of AD, including abnormality of cellular homeostasis and synaptic function, inevitably leading to cell death.…”
Section: Improvement Of Brain Functionmentioning
confidence: 99%